Prognostic Accuracy of the GRACE Score in Octogenarians and Nonagenarians with Acute Coronary Syndromes - Cerqueira Junior,Antonio Mauricio dos Santos (2018)
Abstract Background: The GRACE Score was derived and validated from a cohort in which octogenarians and nonagenarians were poorly represented. Objective: To test the accuracy of the GRACE score in predicting in-hospital mortality of very elderly individuals with acute coronary syndromes (ACS). Methods: Prospective observational study conducted in the intensive coronary care unit of a tertiary center from September 2011 to August 2016. Patients consecutively admitted due to ACS were selected, and the very elderly group was defined by age ≥ 80 years. The GRACE Score was based on admission data and its accuracy was tested regarding prediction of in-hospital death. Statistical significance was defined by p value < 0,05. Results: A total of 994 individuals was studied, 57% male, 77% with non-ST elevation myocardial infarction and 173 (17%) very elderly patients. The mean age of the sample was 65 ± 13 years, and the mean age of very elderly patients subgroup was 85 ± 3.7 years. The C-statistics of the GRACE Score in very elderly patients was 0.86 (95% CI = 0.78 - 0.93), with no difference when compared to the value for younger individuals 0.83 (95% CI = 0.75 - 0.91), with p = 0.69. The calibration of the score in very elderly patients was described by χ2 test of Hosmer-Lemeshow = 2.2 (p = 0.98), while the remaining patients presented χ2 = 9.0 (p = 0.35). Logistic regression analysis for death prediction did not show interaction between GRACE Score and variable of very elderly patients (p = 0.25). Conclusion: The GRACE Score in very elderly patients is accurate in predicting in-hospital ACS mortality, similarly to younger patients.